Brazilian propolis ethanol extract and its component kaempferol induce myeloid-derived suppressor cells from macrophages of mice in vivo and in vitro - Hiroshi Kitamura; Natsuko Saito; Junpei Fujimoto; Ken-ichi Nakashima; Daisuke Fujikura (BMC Complementary and Alternative Medicine, 2018)
Abstract Background Brazilian green propolis is produced by mixing secretions from Africanized honey bees with exudate, mainly from Baccharis dracunculifolia. Brazilian propolis is especially rich in flavonoids and cinammic acid derivatives, and it has been widely used in folk medicine owing to its anti-inflammatory, anti-viral, tumoricidal, and analgesic effects. Moreover, it is applied to prevent metabolic disorders, such as type 2 diabetes and arteriosclerosis. Previously, we demonstrated that propolis ethanol extract ameliorated type 2 diabetes in a mouse model through the resolution of adipose tissue inflammation. The aims of this study were to identify the immunosuppressive cells directly elicited by propolis extract and to evaluate the flavonoids that induce such cells. Methods Ethanol extract of Brazilian propolis (PEE; 100 mg/kg i.p., twice a week) was injected into lean or high fat-fed obese C57BL/6 mice or C57BL/6 ob/ob mice for one month. Subsequently, immune cells in visceral adipose tissue and the peritoneal cavity were monitored using FACS analysis. Isolated macrophages and the macrophage-like cell line J774.1 were treated with PEE and its constituent components, and the expression of immune suppressive myeloid markers were evaluated. Finally, we injected one of the identified compounds, kaempferol, into C57BL/6 mice and performed FACS analysis on the adipose tissue. Results Intraperitoneal treatment of PEE induces CD11b+, Gr-1+ myeloid-derived suppressor cells (MDSCs) in visceral adipose tissue and the peritoneal cavity of lean and obese mice. PEE directly stimulates cultured M1 macrophages to transdifferentiate into MDSCs. Among twelve compounds isolated from PEE, kaempferol has an exclusive effect on MDSCs induction in vitro. Accordingly, intraperitoneal injection of kaempferol causes accumulation of MDSCs in the visceral adipose tissue of mice. Conclusion Brazilian PEE and its compound kaempferol strongly induce MDSCs in visceral adipose tissue at a relatively early phase of inflammation. Given the strong anti-inflammatory action of MDSCs, the induction of MDSCs by PEE and kaempferol is expected to be useful for anti-diabetic and anti-inflammatory therapies. Graphical Abstract